Review of good practices on enhancing the role of corporate reporting in attaining sustainable development goals (UN New YorkUS, 2015)
Highlights the important role of corporate reporting in the development agenda and outlines the main international initiatives and good practices on sustainable reporting. Addresses the key challenges encountered in sustainable reporting that need to be considered to improve its quality and comparability to enhance the role of corporate reporting in attaining the SDGs.
Keywords: ACCOUNTING